A dinâmica do léxico: a neologia de empréstimos no contexto da publicidade - CONTIERO, Elza (Universidade Federal do Pará, 2019)
The influence of globalization and technology on the lexicon of languages is a fact that cannot be denied; therefore the constant occurrence of foreign words in the Brazilian Portuguese language is a linguistic phenomenon that deserves some reflection. Nowadays, English is the language which gives rise to the most lexical borrowings absorbed by the Brazilian Portuguese language. Broad presence of foreign lexical in media channels linked to communication and information can reveal such phenomenon. The main goal of this paper is to analyze the foreign words found in advertising texts, conveyed in magazines whose target audience is the youth. The collected foreign words refer to a neology that has not been yet transformed into a loanword, so to identify them as such; we adopted the lexicographical criteria, dictionary registration. Having said that, we shall consider a foreign word the lexical unit originally of a foreign language and that is in full use in the Brazilian Portuguese language but it is not in the dictionaries yet.